2021
DOI: 10.11594/jaab.02.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Desert locust (Schistocerca gregaria Forskal) and its management: A review

Abstract: The desert locust [Schistocerca gregaria (Forskal)] (Orthoptera: Acrididae) is one of the world’s most dangerous and destructive migratory pests. It is a highly voracious and polyphagous insect. Its swarms can travel hundreds of kilometers per day and infest areas covering millions of square kilometers, resulting in substantial crop losses. We synthesize published research data and reports on the life cycle, behavior, phases, and damage of the desert locust, as well as its possible management practices, in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…It is related to the sex difference in basal breadth and length because the palate of females participates in the grooving process and has a stronger demand for mechanical sensing, particularly for feeling the force required by the palate during the grooving process. This has also been reported in insects such as the desert locust Schistocerca gregaria Forskal (Katel et al, 2021), in which the mandible participates in the grooving process, and there are some behavioral differences between males and females. On the other hand, in the ultrastructural morphology of the mandible, we found that the number of ST I in the female mandible was significantly higher than that in the male mandible.…”
Section: Discussionsupporting
confidence: 57%
“…It is related to the sex difference in basal breadth and length because the palate of females participates in the grooving process and has a stronger demand for mechanical sensing, particularly for feeling the force required by the palate during the grooving process. This has also been reported in insects such as the desert locust Schistocerca gregaria Forskal (Katel et al, 2021), in which the mandible participates in the grooving process, and there are some behavioral differences between males and females. On the other hand, in the ultrastructural morphology of the mandible, we found that the number of ST I in the female mandible was significantly higher than that in the male mandible.…”
Section: Discussionsupporting
confidence: 57%
“…This is because the palate of females is involved in the grooving process and has a greater demand for mechanical sensing, especially for sensing the force required by the palate during the grooving process, so it is related to the sex difference in basal width and length. This has also been reported in insects such as the desert locust Schistocerca gregaria Forskal (Katel et al, 2021), in which the mandible participates in the grooving process, and there are some behavioral differences between males and females. On the other hand, in the ultrastructural morphology of the mandible, we found that the number of ST I in the female mandible was significantly higher than that in the male mandible.…”
Section: Discussionsupporting
confidence: 55%
“…An adequate assessment of the impacts on population livelihood is a complex process (FAO, 2006; Li et al., 2022; Srikrishnan et al., 2022). Desert locust is known for its ability to form massive swarms when their numbers increase (Katel et al., 2021; Song, 2004). In 2019, these swarms originating from Yemen invaded East African countries like Ethiopia, Kenya, and Somalia, destroying over 100,000 ha of crops and pastureland in Ethiopia and Somalia, and 175,000 ha in Kenya (Okonji, 2020; World Bank, 2020).…”
Section: Introductionmentioning
confidence: 99%